Keefektifan Model Pembelaran Inkuiri Berbantuan Media Crithingcle terhadap Berfikir Kritis Siswa Kelas III SD Negeri Plumutan - Tyas Ningrum Puasari; Lisa Virdinarti Putra (Journal on Education, 2024)
The aim of the research is to determine the effectiveness of the crithingcle-assisted inquiry learning model on the critical thinking of class III students at Plumutan State Elementary School. This research uses a quantitative approach with a type of experimental method, namely Quasi Experimental Design with a Non Equivalent Control Group Design design. The population in this study were all third grade students at Plumutan State Elementary School. Data collection techniques use cognitive domain tests, observation, interviews and documentation. The data analysis techniques used are, Independent Sample T-Test and Simple Linear Regression Test, and Paired Sample T-Test. The results of this research show that: (1) there are differences in the use of inquiry learning methods assisted by crithingcle media towards students' critical thinking. This is proven by the results of the Independent Sample T-Test with a significance level of less than 0.05, namely 0.001<0.005. So it can be concluded that there is a significant difference between the experimental class and control class learning groups, where the experimental class's average score is 83.67 which is greater than the control class's average of 78.36. (2) there is an influence of the use of inquiry learning methods assisted by critical thinking media. shiva. This is proven by the Simple Linear Regression Test with a significance value of less than 0.05, namely 0.003<0.05. So, in the student critical thinking variable, it can be concluded that there is an influence of the inquiry learning method assisted by crithingcle media on students' critical thinking (R square value 0.503= 50.3%. (3) there is an increase in the inquiry learning model assisted by crithingcle media. This is proven by the results of the Paired Sample T Test -Test the significance value is less than 0.05, namely 0.000 < 0.05.